2008
DOI: 10.1016/j.clinph.2007.11.176
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the dynamics and origin of epileptic activity in patients with tuberous sclerosis evaluated for surgery of epilepsy

Abstract: Objective: The epilepsies associated with the tuberous sclerosis complex (TSC) are very often refractory to medical therapy. Surgery for epilepsy is an effective alternative when the critical link between the localization of seizure onset in the scalp and a particular cortical tuber can be established. In this study we perform analysis of ictal and interictal EEG to improve such link. Methods: The ictal and interictal recordings of four patients with TSC undergoing surgery for epilepsy were submitted to indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Usually, data from several imaging modalities, such as electroencephalography (EEG), magnetoencephalography (MEG), diffusion tensor imaging (DTI), single-photon emission computed tomography (SPECT), and positron emission tomography (PET) must be integrated for an accurate presurgical localization. MEG (Kamimura et al, 2006; Xiao et al, 2006; Widjaja et al, 2010) or EEG data (Leal et al, 2008; Ochi et al, 2011; Kargiotis et al, 2013) are frequently reported in the literature. Very few reports present simultaneous MEG and EEG recordings (Iida et al, 2005; Sugiyama et al, 2009) in TSC-related pediatric epilepsy patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, data from several imaging modalities, such as electroencephalography (EEG), magnetoencephalography (MEG), diffusion tensor imaging (DTI), single-photon emission computed tomography (SPECT), and positron emission tomography (PET) must be integrated for an accurate presurgical localization. MEG (Kamimura et al, 2006; Xiao et al, 2006; Widjaja et al, 2010) or EEG data (Leal et al, 2008; Ochi et al, 2011; Kargiotis et al, 2013) are frequently reported in the literature. Very few reports present simultaneous MEG and EEG recordings (Iida et al, 2005; Sugiyama et al, 2009) in TSC-related pediatric epilepsy patients.…”
Section: Introductionmentioning
confidence: 99%
“…Few other studies report mixed pediatric and adult patient cohorts (Jansen et al, 2006; Wu et al, 2006; Canuet et al, 2008). For source analysis, previous investigations of epileptic foci in TSC patients used various methods for the identification of the epileptic active areas, such as synthetic aperture magnetometry (SAM) (Xiao et al, 2006; Sugiyama et al, 2009), equivalent current dipoles (ECDs) (Iida et al, 2005; Kamimura et al, 2006; Wu et al, 2006; Xiao et al, 2006; Leal et al, 2008; Sugiyama et al, 2009; Widjaja et al, 2010), or multiple signal classification (MUSIC) (Jansen et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…This study provides additional support for the contention that componential analysis and source localization methods can be used successfully for noninvasive source localization of ictal activity (Lagerlund et al, 2004;Leal et al, 2006Leal et al, , 2008. In the current study, the sample consisted of five patients who had focal temporal lobe epilepsy with a single epileptic focus as confirmed by a seizure-free history following surgery.…”
Section: Discussionmentioning
confidence: 91%
“…It means that each projection [LΓ 1/2 ] k to measurement space is equally many standard deviations away from the mean, which is zero. This is equivalent to Z-scores [39,41], where a set of Gaussian random variables from different scales are unified to ensure a fair comparison.…”
Section: Standardized Low-resolution Brain Tomography As Probabilisti...mentioning
confidence: 99%